Risk Management Strategies for the Banking Sector to Cope with the Emerging Challenges - Tomer Kedarya; Amir Elalouf (Foresight and STI Governance)
The banking industry is facing unprecedented challenges, including cybersecurity threats, the need for rapid technology upgrades, a high degree of uncertainty, aggressive entry of technology giants into the financial market, and others. Like most traditional sectors, banks are trying to keep up with the pace of change, monitor emerging risks, and adjust their development strategies. The article analyzes the emerging trends for the banking sector globally and, in particular, in the context of Israel. Interviews with representatives of the most influential national banks formed the information basis of the study. Shifts in corporate strategies, requests for new business models and «working with the future» were identified. The results emphasize the importance of an integrated, holistic approach to risk management and may be useful for banks not only in Israel, but also in other countries and regions.